Signal enhancement of FBG-based cantilever accelerometer by resonance suppression using magnetic damper - Udos, Waldo; Lee, Yen Sian; Lim, Kok Sing; Ong, Zhi Chao; Zaini, Muhammad Khairol Annuar; Ahmad, Harith (Elsevier, 2020)
In this work, we propose the use of a magnetic damper in the FBG-based cantilever accelerometer (FCA) to reduce the distortion of signal due to the infinite signal amplification at the resonant frequency. The magnetic damper comprises a permanent magnet and a U-shape aluminum structure. The permanent magnet serves as a load and is attached to one end of the cantilever whereas the aluminum structure serves as a damper to suppress the cantilever resonance. In the experiment, it is found that the distortion on the detected signal by FCA is reduced when the damper is incorporated, and the detected signal has a higher cross-correlation coefficient (CCC) with a reference signal from a standard capacitive based accelerometer. The introduction of a magnetic damper enables the vibration detection of the FCA in the resonant frequency region with reduced signal distortion and it widens the detection range of the FCA. © 2020 Elsevier B.V.